2012
DOI: 10.4049/jimmunol.1200936
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 Produced by Induced Regulatory T Cells (iTregs) Controls Colitis and Pathogenic Ex-iTregs during Immunotherapy

Abstract: “Natural” regulatory T (nTreg) cells that express the transcription factor Foxp3 and produce IL-10 are required for systemic immunological tolerance. “Induced” Treg (iTreg) cells are non-redundant and essential for tolerance at mucosal surfaces, yet their mechanisms of suppression and stability are unknown. We investigated the role of iTreg cell-produced IL-10 and iTreg cell fate in a treatment model of inflammatory bowel disease. Colitis was induced in Rag1−/− mice by the adoptive transfer of naïve CD4+ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 57 publications
(59 reference statements)
3
74
1
2
Order By: Relevance
“…Activated MAPKs phosphorylate the transcription factors AP-1 (c-Jun) and CREB, which subsequently leads to the secretion of proinflammatory cytokines such as IL-6, TNF-a, as well as the expression of the anti-inflammatory cytokine IL-10 (33,34). In this study, we have clearly demonstrated that LPS induces the activation of MAPKs (p38 and ERK1/2) and subsequent activation of AP-1 and CREB observed by its phosphorylation.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Activated MAPKs phosphorylate the transcription factors AP-1 (c-Jun) and CREB, which subsequently leads to the secretion of proinflammatory cytokines such as IL-6, TNF-a, as well as the expression of the anti-inflammatory cytokine IL-10 (33,34). In this study, we have clearly demonstrated that LPS induces the activation of MAPKs (p38 and ERK1/2) and subsequent activation of AP-1 and CREB observed by its phosphorylation.…”
Section: Discussionmentioning
confidence: 58%
“…Additionally, mutations in IL-10 and IL-10 receptors result in severe infantile inflammatory bowel disease (34). Of note, intestinal macrophages are potent producers of IL-10, which in turn increases the Treg population by maintaining stable Foxp3 expression (33). It is tempting to speculate that IL-10 secreted by TM in vivo helps to maintain the testicular population of Tregs, which are known to be relevant for the establishment of testicular immune privilege (42).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, iTregs can be generated rapidly in large numbers and constitute a promising alternative choice for adoptive transfer (15,17). However, the instability of Foxp3 expression within iTregs and their potential to revert to pathogenic Teffs remain a concern and have represented major limitations (18,42). Attempts to improve the stability of Foxp3 expression within iTregs have yielded only limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the maintenance of Foxp3 expression in Tregs tends to be unstable within an inflammatory milieu, and IL-10 may reverse this process (42,55,57). In the current study, we demonstrate that the loss of Foxp3 in iTregs following adoptive transfer correlates with proliferation, and the concurrent administration of RAPA attenuates this process.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a protective role for B cells and serum Ig was described in the TCR-α -/-spontaneous model of colitis (22) and DSS induced colitis (23). And also, Tregs are considered one of the most important immune cell regulators of intestinal homeostasis (15,(24)(25)(26)(27). Thus, the deficiency of GALT B cells and Tregs during 3.5% DSS may cause the infiltration of CD11b + cells and lead to an irreversible colitis.…”
Section: Resultsmentioning
confidence: 99%